Exercises for strength and its impact in terms of some of the variables Kenmatic hit the ball in baseball - Abedulkareem, Sareeh; Salah, Bashar (Journal of Physical Education, 2015)
It came the importance of research to focus on the training task force to develop some Elkinmetekih variables for baseball players batters ball and associated exercises based on the plucks the principle of using different resistances of the muscles working to stage hit and within the skill performance during the beating and find out the extent of their impact in the development of some Elkinmetekih beaten variables, and defined the research problem of During the exercise researcher baseball as a player for the national team, he wanted to go into the study Elkinmetekih variables to the skills of the game, especially hitting the ball skill that poses a significant proportion to influence the result of the competition, as it has never been addressed this game study and research and fact at the level of the country of Iraq, On the other hand, benefit from the results of Elkinmetekih variables in the preparation of workouts the fact that most of the skills of the game are related to capacity physical task to achieve the place hit the ball bat, that achieve the best performance and the best flight path of the ball, which helps to win the round and the game, and the aim of the message to identify some Elkinmetekih variables and prepare especially so training and identify the impact of these exercises it, and I suppose researcher ecstasy statistically significant differences between tribal tests and post variables Elkinmantekah skill to hit the ball to the research sample differences, in Part III, the researcher used the experimental method and represent the research community and appointed by the way intentional and consisting of (8) players Dharban ( Club Baghdad) and representing the research community overall by (100%), has identified the Elkinmetekih variables used percentage, mean, standard deviation, test (T-test) of the samples associated with, the researcher concluded that the exercises set affected the speed of the starting ball players hitters in Baseball, and recommended use of the exercises and their impact on other variables Kinmetekih